First insight into temporal variation of digestive enzyme activities in flathead grey mullet (Mugil cephalus) during the ongrowing phase - Silvia Natale; Andrea Bertini; Enric Gisbert; Karl B. Andree; Elisa Benini; Dario Vallainc; Pier Paolo Gatta; Alessio Bonaldo; Luca Parma (Aquaculture Reports)
Digestive enzymes break down the complex nutrients of food into easily absorbable molecules. Understanding their temporal variation during food transit through the gastrointestinal tract is crucial for developing effective nutritional strategies. This study provides the first insight on the digestive capacity of captive flathead grey mullet (Mugil cephalus), a promising omnivorous/detritivorous species for the sustainable diversification of aquaculture in EU. Fish (initial weight: 67.90 ± 15.46 g) were reared in captivity and fed a low fish meal-based diet for 113 days. At the end of the trial, the activity of pancreatic and intestinal enzymes were analysed at three different times: 0, 6 and 12 hours post-prandial. Additionally, the gene expression of pept1 was determined in the intestine at all considered times to provide a reference to peptide absorption. Alkaline proteases, trypsin and chymotrypsin showed a significant increase at 6 hours post-prandial, with values markedly lower than those of α-amylase. Bile salt-activated lipase and leucine-alanine aminopeptidase increased at 12 hours post-prandial. In the anterior intestine, aminopeptidase presented higher activity at 6 hours post-prandial while alkaline phosphatase showed no significant differences in both anterior and posterior tracts. Pept1 expression was significantly higher at 12 hours post-prandial in the posterior intestine. This study provides essential insights into the digestive physiology of captive-reared, ongrowing flathead grey mullet (Mugil cephalus), emphasizing the importance of aligning feeding practices with the species’ unique digestive adaptations. These findings establish a foundation for optimizing feeding schedules and diet composition to significantly enhance nutrient absorption and growth efficiency.